Highly Diastereoselective NHC-Catalyzed [4+3] Annulation of Enals, Aldehydes and N-Phenyl Urea/Thiourea for the Synthesis of Monocyclic trans-1,3-Diazepanes - Siddiqui, Ibadur R.; Srivastava, Anjali; Shamim, Shayna; Srivastava, Arjita; null; Waseem, Malik A.; Singh, Rana K. P. (Synlett, 2013)
N-Heterocyclic carbene catalyzed synthesis of 1,3-diazepanes from α,β-unsaturated aldehydes, N-phenyl urea/thiourea and aromatic aldehydes has been developed. The reactive Breslow intermediate, formed by reaction of the enal with the NHC, attacks as a d3 nucleophile at the 1-arylidene-3-arylurea derivative, which is produced by simple reaction of N-phenyl urea/thiourea with an aromatic aldehyde. The resulting intermediate, on subsequent heterocyclization, forms the product with high yield. The reaction proceeded smoothly with high atom economy, producing a new C–C and a new C–N bond in a one-pot operation.
Keywords: N-heterocyclic carbene; diastereoselective; 1,3-diazepane; multicomponent; one-pot reaction